EVALUATION OF AN ARCTIC ICE-FREE LAND SITE AND RESULTS OF C-130 AIRCRAFT TEST LANDINGS. POLARIS PROMONTORY, NORTH GREENLAND 1958-1959 - NEEDLEMAN,STANLEY M.; KLICK,DONALD W.; MOLINEUX,CARLTON E. (1961)
Fiel investigations of an ice-free land area at Polaris Promontory, Hall Land in northwest Greenland were undertaken to determine if this area could support austere military aircraft operations. Detailed scientific observations of the geology, meteorology, and natural terrain features of the area were made, thorough investigations of the soil features and bearing strength were conducted, and an airstrip was prepared and marked. Successful test landings by a C-130 aircraft were made on the airstrip. Possible alternate airstrip sites were studied and conclusions drawn on the usability of such ice-free land sites for military activities. The selection of specific sites in such areas by lowaltitude aerial reconnaissance and applied photogeologic interpretation methods is feasible and practical. Such techniques, when employed by professionals with considerable field experience in the Arctic regions, are reliable, rapid, and inexpensive. (Author)